Brain MRI Findings in Coenurosis: A Helminth Infection. Issue 3 (18th February 2020) - Kulanthaivelu, Karthik; Bhat, Maya D; Prasad, Chandrajit; Srinivas, Dwarakanath; Mhatre, Radhika; Nandeesh, Bevinhalli N
ABSTRACT: BACKGROUND AND PURPOSE: Parasitic neuroinfections in humans have etiological agents spanning a broad spectrum from unicellular (protozoan) to multicellular helminthic (metazoan) organisms. Cerebral coenurosis is a rare cestodal helminthic infection caused by Taenia multiceps . The neuroimaging features of this entity were reviewed to discern an imaging phenotype. METHODS: Retrospective analysis was performed on 6 cases of cerebral coenurosis, whose diagnoses were confirmed by histopathology. The clinical, imaging, and histopathological features were recorded for analysis. RESULTS: Clinical expressions included focal neurological deficit due to mass effect ( n = 4), intraventricular obstruction with features of raised intracranial tension ( n = 1), headache ( n = 3), seizures ( n = 3), and incidental lesions ( n = 1). One patient presented with recurrence 1 year after surgical excision. Neuroimaging revealed cystic thin‐walled lesions with clustered eccentric internal nodules corresponding to the plenitude of protoscolices of the tapeworm. Three of the lesions showed a multilocular cystic morphology. Spectroscopic metabolite signature of alanine and succinate commensurate with the parasitic etiology was remarkable in the lesions. Enhancement and edema inversely correlated with the signal suppression on fluid‐attenuated inversion recovery (FLAIR) imaging. The lesions had a predominantly juxtacortical distribution. CONCLUSIONS: In an appropriate clinical setting, a cystic lesion with clustered eccentric internal nodular foci ought to raise the suspicion of this rare infection. Magnetic resonance spectroscopic signature of succinate and alanine, if present, further strengthens the likelihood of coenurosis. Signal characteristics, wall enhancement, and perilesional edema may vary, possibly determined by the stage in the evolution of the parasite.